PENYULUHAN TENTANG TEKNIK PIJAT EFFLEURAGE TERHADAP PENGURANGAN RASA NYERI PERSALINAN KALA I - Septa Dwi Insani; Husna Sari; Marlen Sadrina Sitepu; Erlina Hayati; Mutiara Dwi Yanti; Tetty Junita Purba (Jurnal Pengabdian Masyarakat Putri Hijau, 2021)
The research was aimed at to understand the effect massage Back-Effleurage technique to reduce labor pain at first stage in the Kurnia’s maternity clinic Delitua district Deli Serdang Regency. The research using quantitative analytical methods with a Quasi-Experimental research design with a One Group Pretest-Posttest approach. The data collection technique used an observation sheet. This massage Back-Effleurage technique is carried out for 20 minutes/hour during contractions. The sampling technique used was Total Sampling method. Paired Sample T Test is used for data analysis. The population in this research were 25 pregnant women who entered the Trimester III as many as 25 of pregnant women. The result of this research showed that giving the massage Back-Effleurage technique on the abdomen in the Kurnia’s maternity clinic can reduce labor pain from the one the mother experiences with moderate pain become mild pain and mother who experiences severe pain become moderate pain with p value = 0,000 (p<0,05). It can concluded the there is a significant effect by giving massage Back-Effleurage techniques to reduce labor pain at first stage